Antibacterial activity of two varieties of water chestnuts (Trapa sp.) (Journal of Bio-Science, 2014)
Context: Water chest nut (Trapa sp.), an aquatic fruit plant has been used in some area of the rural people of Bangladesh for the treatment of some chronic diseases. Objective: The main objective of this study is to investigate the antibacterial activities of the two varieties (red and green) of water chest nuts. Material and Methods: The antibacterial activities of the methanol extracts of two varieties of water chestnut fruits were studied against a number of human pathogenic bacterial species by using the disc diffusion method. The antibiotic Kanamycin (30 ?g) was used as standard. Results: The methanol extract of red variety of water chestnut showed high antibacterial potential (31 mm) against Bacillus subtilis at concentration of 600 ?g. On the other hand, green variety showed highest antibacterial activities (12 mm) against Staphylococcus aureus at concentration of 600 ?g. In disc diffusion assay, the methanol extract of red variety was found to have a significant antibacterial efficiency as compared to the methanol extract of green variety of water chestnut. Conclusion: These findings pinpoint the efficiency of these extracts to inhibit microbial growth. It may lead to the development of a new phyto-medicine. DOI: http://dx.doi.org/10.3329/jbs.v20i0.17725 J. bio-sci.  20:  115-123, 2012